Detection of SARS-CoV-2 Genes in Stool Samples of COVID-19 Survivors Using the Real-Time Reverse Transcriptase Polymerase Chain Reaction Method - Ka’bah; Nur Laela Alydrus; Arlitha Dekayana; Kasmuddin; Rinaldi Indra Duma’ari (HM Publisher, 2024)
The spread of a pneumonia outbreak infected with the new coronavirus (COVID-19) from Wuhan, China, has spread globally. Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has been identified as the pathogen responsible for the pneumonic plague. The angiotensin conversion enzyme (ACE2) is the cellular receptor for SARS-CoV-2 entry. ACE2 is highly expressed in the epithelium of the stomach, duodenum and rectum. In infected patients, some patients infected with SARS-CoV-2 experience unusual symptoms, namely gastrointestinal symptoms, namely diarrhea, nausea and vomiting. This study aims to detect the presence of the SARS-CoV-2 gene in stool samples from COVID-19 survivors using the method real time RT-PCR as the gold standard for confirming COVID-19 with the RdRp and Helicase (ORF1b) target genes. There were 12 samples of COVID-19 survivors who met the inclusion criteria. The results showed that of the 12 samples, 2 samples were positive for SARS-CoV-2 RNA with Ct values of 32.79 and 36.86 which were detected on days 18 and 22 days after their respiratory tract tests were negative.